Anti-acanthamoebic activity of methanolic extract of Piper sarmentosum leaves - Mustafa, Farah Farisha; Ghazali, Nor Farahiyah; Mohamad, Habsah; Ibrahim, Maizatul Akma; Zakaria, Nor Hafizah (Malaysian Society for Microbiology, 2021)
Aims: Piper sarmentosum or locally known as Kaduk, is a tropical herb plant that was investigated for its phenolic content by previous researchers. The present study aimed at the analysis of crude methanolic extract of P. sarmentosum leaves for phenolic compounds identification and its anti-amoebic properties against pathogenic Acanthamoeba castellanii.